Penerapan ISAK No.35 Pada Laporan Keuangan Masjid At-Taqwa - Sri Wahyuni; Yulinartati; Ari Sita Nastiti (LPPM POLITEKNIK LP3I BANDUNG, 2023)
This study aims to analyze the financial statements of the At-Taqwa Wonoasri Mosque, so that it can be seen how in recording the financial statements of the At-Taqwa Wonoasri Mosque and introduce the financial standards of non-profit organizational entities, namely ISAK No. This study used a qualitative method which was carried out by direct observation and interviews with the administrators of the Wonoasri At-Taqwa Mosque. The results of this study indicate that the form of the report at the At-Taqwa Wonoasri Mosque is not in accordance with the applicable non-profit organization standards, namely ISAK No. 35. this is due to lack of updates in knowledge related to non-profit organization entity standards. The mosque's financial statements are analyzed based on ISAK No. 35 which consists of five components of financial statements, namely statements of financial position, comprehensive reports, reports of changes in net assets, statements of cash flows and notes to financial statements. Based on this research, it can be concluded that the basis of recording applied at the At-Taqwa Wonoasri Mosque is using a cash basis. After the analysis, it is known that the mosque's financial statements are not in accordance with ISAK No. 35. Then the mosque's financial statements were reconstructed in accordance with ISAK No. 35 by identifying transactions, making general journals, posting to ledgers, asset depreciation paragraphs, adjusting ledgers, trial balances.